Endovascular Treatment of Symptomatic Thoracic Aneurysm Due to Periaortic Lymphoma - Raupach, Jan; Vales, Jan; Vojacek, Jan; Hoffmann, Petr; Lojik, Miroslav; Kamaradova, Katerina; Cabelkova, Pavla; Chovanec, Vendelin; Renc, Ondrej; Krajina, Antonin; Maly, Radovan (Vascular and endovascular surgery, 2018)
An aggressive periaortic lymphoma could very rarely invade the aortic wall. We present a unique case of a patient with symptomatic thoracic aneurysm and imminent rupture due to the periaortic lymphoma, in which endovascular treatment using stent graft was applied. After stabilization of the aorta and histological confirmation of aggressive B-cell lymphoma by computed tomography-guided biopsy, the antilymphoma therapy was initiated. Despite the full treatment, the patient died 12 months later.
Keywords: CT angiografie; invazivní růst nádoru; Neoplasm Invasiveness; Blood Vessel Prosthesis Implantation; Blood Vessel Prosthesis; Humans; Positron Emission Tomography Computed Tomography; aneurysma hrudní aorty; PET/CT; Computed Tomography Angiography; Fatal Outcome; cévy - implantace protéz; Aorta, Thoracic; ultrazvukem navigovaná biopsie; Aortography; stenty; aorta thoracica; fatální výsledek; mužské pohlaví; B-buněčný lymfom; aortografie; Disease Progression; Endovascular Procedures; endovaskulární výkony; výsledek terapie; Lymphoma, B-Cell; cévní protézy; Stents; Treatment Outcome; lidé; Aortic Aneurysm, Thoracic; Aged; senioři; progrese nemoci; Male; Image-Guided Biopsy